PENDIDIKAN KARAKTER PADA ANAK BERKEBUTUHAN KHUSUS - Muchamad Suradji (TA'LIM : Jurnal Studi Pendidikan Islam, 2019)
This study aims to determine the character education of children with special needs in SDLB 45 Babat Lamongan. The research method used in this study is qualitative, while the data collection techniques are observation, interview and documentation. The analysis in this study uses descriptive qualitative analysis with stages of data display, data reduction, and verification and conclusions. The results of the research conducted, it can be concluded that the character values ​​applied to students at SDLB 45 are curiosity, friendly / communicative and care for the environment. 3 out of the 18 character values ​​that exist when applied can be considered good, although the implementation process requires a little time. This is because students are different from normal students in general, and the teacher implements gradually by providing stimulus in advance and demonstrating that the character values ​​to be conveyed can be received by students well.